Hybrid technique combining photoelasticity and boundary element method for stress analysis - Sridharan, N.; Kesavan, K.; Parivallal, S.; Ravisankar, K. (Journal of Structural Engineering, 2025)
This paper presents a hybrid method of stress analysis, in which the experimentally determined boundary stresses from a photoelastic experiment are used in the boundary element method (BEM) of analysis. Experimentally measured stresses are more reliable whereas numerical techniques are amenable to computers for quick processing. Hence, an experimental - numerical combination makes use of both the methods advantageously. In the present investigation, the principal stresses are obtained at the boundary points from a photoelastic experiment conducted on a wall panel model (epoxy model) . These values are subsequently used in BEM to get the distribution of the first stress invariants (sum of principal stresses) at the interior points of interest of the wall panel model. These stresses along with difference in principal stresses (isochromatic fringe order) obtained from the same photoelastic experiment at the points of interest in the wall panel model are used for separating the stresses and the results are compared with those obtained using a similar hybrid method of analysis involving finite difference method (FDM)- photoelastic (experimental) combination.